Experimental and numerical studies on compressive mechanical properties of hollow-sphere structures with perforations. (July 2019) - Dai, Meiling; Ma, Yinhang; Yang, Fujun; He, Xiaoyuan
Highlights: Compressive mechanical properties of PHSSs are studied through experiments and numerical simulations. In experiment, the PHSSs in BCC arrangement were produced by 3D printing technology. The deformation of multi cell structure includes linear elastic, large deformation and densification stages. Effects of structural geometric properties on the Young's modulus and initial yield stress of PHSSs are analyzed by using FEM. The stiffness and strength of the FCC structure are superior to those of the BCC or SC structure. Abstract: The compressive mechanical properties of perforated hollow-sphere structures (PHSSs) are studied through experiments and numerical simulations. In a PHSS, hollow spheres perforated with several holes, which are to open the inner volumes and surface areas of the hollow spheres, are connected in simple cubic (SC), body centered cubic (BCC) or face centered cubic (FCC) pattern. In experiments, the unit cell and multi cell structures in the BCC arrangement are fabricated through 3D printing technology, and the results indicate deformation behaviors similar to those of classic hollow-sphere structures. Then, the effects of geometric properties, such as wall thickness, hole diameter, linking neck radius, and the spatial arrangement of the spheres, on the structural Young's modulus and initial yield stress are calculated and analyzed using the finite element method (FEM). Finally, the relationships between the mechanical properties and relative densities of different sphere arrangements are also obtained by nonlinear fitting.